FAKTOR RISIKO TERJADINYA HEPATITIS B PADA IBU HAMIL DI KABUPATEN PURBALINGGA : CASE CONTROL STUDY - Shalsabilla, Zulfa; Rini, Bekti Aribawanti; Suhartono, Suhartono; Muh, Fauzi (Jurnal Epidemiologi Kesehatan Komunitas, 2025)
Background: Hepatitis B is a liver infection with the potential to become chronic and lead to death. The prevalence of Hepatitis B in Purbalingga Regency remains above the targets set by the 2020-2024 RPJMN and SDGs 3.3.4, which aim to reduce the incidence of Hepatitis B to 0.1% by 2030. This study analyze the risk factors for Hepatitis B among pregnant women in Purbalingga Regency.Methods: This study employed a case-control design with an accessible population. The accessible population comprised all pregnant women, both HBsAg reactive and non-reactive, recorded in the SIHEPI application of the Purbalingga District Health Office between January 2023 and September 2024, totaling 112 pregnant women. The sample in this study consisted of the entire accessible population. Data were analyzed using the Chi-Square test and logistic regression. Results: This study identified four variables significantly associated with the occurrence of Hepatitis B in pregnant women: maternal knowledge (p-value = 0.032, OR = 2.33 [1.08-5.05]), family history of Hepatitis B (p-value = 0.001, OR = 2.331 [1.076-5.049]), sharing nail clippers (p-value = 0.022, OR = 2.35 [1.13-4.89]), and sharing razors (p-value = 0.011, OR = 2.469 [1.228-4.963]).Conclusion: Risk factors for Hepatitis B among pregnant women include maternal knowledge, a family history of Hepatitis B, sharing nail clippers, and sharing razors. To prevent Hepatitis B transmission, policymakers should implement early detection for family members of HBsAg-reactive pregnant women.